2017
DOI: 10.1111/tmi.12852
|View full text |Cite
|
Sign up to set email alerts
|

Physical function, grip strength and frailty in people living with HIV in sub‐Saharan Africa: systematic review

Abstract: Objective To present the current knowledge on physical function, grip strength and frailty in HIV-infected patients living in sub-Saharan Africa, where the phenomenon is largely underestimated. Methods A systematic search was conducted on Medline, Scopus and African Index Medicus. We reviewed articles on sub-Saharan African people living with HIV (PLHIV) >18 years old, published until November 2016. Results Of 537 articles, 13 were conducted in six African countries and included in this review. Five articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…Despite these factors, survival has improved with expansion of free ART to treat millions of PLWH in LMIC. However, as these individuals age, they are at higher risk for noncommunicable diseases compared with HIV-negative individuals (206,212), and the prevalence of chronic comorbidities and disability in PLWH in LMIC is increasing dramatically (28,271).…”
Section: Pulmonary Diseases In People Living With Hiv In Low-and Middle-income Countriesmentioning
confidence: 99%
“…Despite these factors, survival has improved with expansion of free ART to treat millions of PLWH in LMIC. However, as these individuals age, they are at higher risk for noncommunicable diseases compared with HIV-negative individuals (206,212), and the prevalence of chronic comorbidities and disability in PLWH in LMIC is increasing dramatically (28,271).…”
Section: Pulmonary Diseases In People Living With Hiv In Low-and Middle-income Countriesmentioning
confidence: 99%
“…In this review, we selected original sarcopenia studies which adopted one of the above-mentioned sarcopenia operational definitions. We are aware that there are a large body of literature that has assessed and described the characteristics of muscle mass or function in PLHIV, variables which were usually impaired compared with people without HIV [7,26,27]. But because these variables have been assessed separately, or studies did not employ a cut point to classify subjects with low or normal range, these studies were not included in this review.…”
Section: Sarcopenia Definitionmentioning
confidence: 99%
“…Among these causes and mechanisms, one factor that may exert influence on sarcopenia prevalence in lower resource settings is malnutrition, given that a higher BMI appears to protect against the development of sarcopenia in PLHIV. There are not studies of sarcopenia (as it is current defined) that have been conducted in lowincome countries, but studies investigating muscle function in low-income African countries have demonstrated a strong link between muscle strength and nutritional status of PLHIV [27,65].…”
Section: Traditional and Hiv-related Risk Factors Contribute To The Dmentioning
confidence: 99%
“…An index of frailty, originally designed to assess older adults, comprising unintentional weight loss, slow walking speed, low grip strength, self‐reported exhaustion and low energy expenditure , predicts morbidity and mortality among American and European HIV patients . The limited data on frailty and grip strength among HIV‐infected persons in sub‐Saharan Africa have recently been reviewed . The few prior studies have found that HIV infection is a risk factor for frailty among South Africans and for low grip strength among Ethiopian adults .…”
Section: Introductionmentioning
confidence: 99%